2007
DOI: 10.3171/foc.2007.22.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Pressure: More Than a Number

Abstract: ✓Many doctors involved in the critical care of head-injured patients understand intracranial pressure (ICP) as a number, characterizing the state of the brain pressure–volume relationships. However, the dynamics of ICP, its waveform, and secondarily derived indices portray useful information about brain homeostasis. There is circumstantial evidence that this information can be used to modify and optimize patients' treatment. Secondary variables, such as pulse amplitude and the magnitude of slow waves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 41 publications
1
74
0
6
Order By: Relevance
“…It has been suggested that, after TBI, NICU treatment should become individualized based on each patient's CPP opt . 2,9 The CPP opt for a patient can be defined as the CPP that minimizes PRx: i.e., maximizes vascular pressure reactivity. There were no ISP or SCPP targets in our studies because we have not yet determined the optimal ISP and SCPP after TSCI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, after TBI, NICU treatment should become individualized based on each patient's CPP opt . 2,9 The CPP opt for a patient can be defined as the CPP that minimizes PRx: i.e., maximizes vascular pressure reactivity. There were no ISP or SCPP targets in our studies because we have not yet determined the optimal ISP and SCPP after TSCI.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a transfer function assumes that a linear transmission occurs from the input to the output signals. This assumption may not be valid for biological signaling, particularly in various disease states (Czosnyka et al, 2007). Another drawback of using these conventional methods is that they are time-invariant and are, therefore, not capable of tracking signal evolution over time.…”
Section: Transfer Function Between Cap and Ecpmentioning
confidence: 99%
“…It has been argued that the amplitude of the fundamental component is useful in evaluating certain indices of cerebrospinal dynamics (Czosnyka et al, 2007).…”
Section: Transfer Function Between Cap and Ecpmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,10,14 Analysis of ICP and CSF dynamics studies were conducted with ICM+ software (Cambridge University Enterprise, Ltd.). 17 The median correlation coefficient between pulse amplitude and ICP (RAP), amplitude of ICP pulse (1 harmonic sine wave), slow wave amplitude (using the morphological clustering and analysis of ICP pulse [MOCAIP] algorithm), and mean ICP values were recorded and calculated during OVM according to the protocols of Czosnyka et al and Kasprowicz et al 2,3,9 LIFT yielded baseline and plateau values of ICP and pulse amplitudes as well as resistance of CSF outflow (ROut). Furthermore, the ICP amplitude quotient (AMP Q) was defined as the quotient between baseline and plateau ICP pulse wave amplitudes.…”
mentioning
confidence: 99%